Karl Marx : a nineteenth-century life - Sperber, Jonathan, 1952- (Liveright Pub. Corp., 2013)
A biography of the philosopher and political revolutionary describes his childhood and family life along with his public life as an agitator and dissident and compares him to his contemporaries.